Prosedur Jasa Pengiriman Barang pada PT. Wahana Prestasi Logistik - Eira Nabilah Rasyiqah Puteri; Sutini Sutini (Jurnal Pengabdian Masyarakat, 2024)
Freight forwarding services do have an important role in economic growth, especially in freight transport using airplanes. Transportation that is getting better and developing rapidly and supported by the advancement of science and technology today, many domestic freight forwarding companies are also established. Where a company sends the goods in its handling in addition to using sophisticated facilities and infrastructure, the company also needs cooperation with other parties to expand the network and performance system of the company to be better in its handling. Therefore, there is also a lot of competition between companies in the field of freight forwarding services in selling their products to consumers, but not everyone can build a freight forwarding company properly, because to place a company in the domestic freight forwarding industry must be able to have professional human resources, and high work standard capabilities, if they want to get the best access to the market and trust from consumers. This development has caused many problems that must be immediately addressed by freight forwarding companies in order to maintain their business, especially to increase revenue in the sales function. Such conditions have caused companies to work hard to capture the market, through a coordinated organizational structure, high specialization, and the ability of management to work effectively and efficiently.